Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Media Wordwall terhadap Hasil Belajar IPAS Siswa Kelas IV di SDN 4 Kuranji - Aulia Salsabiela; Muhammad Makki; Aisa Nikmah Rahmatih (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the low science learning outcomes of fourth-grade students at SDN 4 Kuranji, which were attributed to low learning motivation and limited student engagement due to the lack of variety in instructional media and the limited integration of technology in the learning process. This study aimed to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Wordwall media on students' science learning outcomes in the topic "States of Matter and Their Changes." This research employed a quantitative approach using a pre-experimental research design with a one-group pretest-posttest design. The sample was selected using a saturated sampling technique, involving all members of the population as participants, namely all 30 fourth-grade students at SDN 4 Kuranji. Data were collected through achievement tests, classroom observations, and teacher and student response questionnaires, and were analyzed using a paired-sample t-test. The results revealed that the calculated t-value (16.203) was higher than the critical t-value (2.045). In addition, the significance value (2-tailed) was < .001, which was lower than the significance level of 0.05. Therefore, the null hypothesis (H₀) was rejected, while the alternative hypothesis (Hₐ) was accepted. These findings indicate that the implementation of the Teams Games Tournament (TGT) cooperative learning model assisted by Wordwall media, which has rarely been applied to the topic of States of Matter and Their Changes, can serve as an innovative alternative for improving elementary school students' science learning outcomes. Furthermore, the findings highlight the importance of employing interactive, technology-assisted learning models to enhance students' motivation, encourage active participation in the learning process, and create meaningful learning experiences.